First report of human rotavirus G8P[4] gastroenteritis in India: Evidence of ruminants‐to‐human zoonotic transmission1. Issue 3 (21st December 2012) - Mukherjee, Anupam; Mullick, Satarupa; Deb, Alok Kumar; Panda, Samiran; Chawla‐Sarkar, Mamta
Abstract Group A rotaviruses are the major cause of childhood gastroenteritis worldwide. Due to close proximity of human and cattle in rural areas of developing countries like India, interspecies transmission or zoonotic transmission is a major source of rapid generation of reassortants and genetic or antigenic variants. Previously, many human group A rotaviruses were found with porcine or bovine characteristics from eastern and north‐eastern India. In this study, four unusual human G8P[4] strains were identified which had artiodactyl‐like origins. During an ongoing community based surveillance for epidemiological profiling of diarrheal pathogens, these unusual human group A rotavirus G8P[4] strains were detected from the stool samples of 3–14 months old children with acute diarrhea in Sonarpur, eastern India. Analysis of eleven complete and/or partial gene segments of these unusual G8P[4] strains were done by reverse transcription‐PCR (RT‐PCR) followed by nucleotide sequencing and phylogenetic analysis. The VP7 nucleotide sequences revealed a close phylogenetic relationship to the G8P[7] porcine strain D‐1 and bovine strain KJ59‐2 from South Korea. Whereas the VP4 gene segments were also related closely to human rotavirus prototype strain DS‐1. Other nine gene segments of these G8P[4] rotaviruses were related closely to either animal or animal‐derived rotavirus members of the DS‐1‐like family. These results suggest that origin of these G8P[4] strains might have been resulted from multiple reassortment events between artiodactyls and ruminant‐derived reassortant human rotaviruses. To date, this is the first report of G8P[4] rotavirus from India and the first genomic analysis of G8P[4] strains from Asian continent. J. Med. Virol. 85:537–545, 2013. © 2012 Wiley Periodicals, Inc.